Modulation of cell cycle progression and of antibody production in mouse hybridomas by a nucleotide analogue - Franěk, František (Kluwer Academic Publishers, 1998)
The nucleotide analogue 9-[2-(phosphonomethoxy)ethyl]guanine (PMEG) has been identified as a powerful antiproliferative substance when acting on hybridoma cells. In the range of 10 nM to 100 nM concentrations this agent reduces cell growth rate, while its apoptosis-inducing activity is marginal. Marked induction of apoptosis can be observed at micromolar and higher order concentrations. In PMEG-supplemented media the cell cycle progression is perturbed, the flow-cytometric DNA profile shows a higher proportion of cells in the S and G2/M phases of the cell cycle. Concomitantly with the reduction of the growth rate, the specific monoclonal antibody production rate may rise by 20–27%. Addition of PMEG at the end of the exponential phase of a batch culture results in an enhancement of the final monoclonal antibody concentration.